177Lu-DOTATATE and 177Lu-prostate-specific membrane antigen therapy in a patient with advanced metastatic radioiodine-refractory differentiated thyroid cancer after failure of tyrosine kinase inhibitors treatment - Assadi, Majid; Ahmadzadehfar, Hojjat (World Journal of Nuclear Medicine, 2019)
Patients with radioiodine-refractory differentiated thyroid cancer (RrDTC) have only a limited or no benefit from radioiodine therapy. For these patients, tyrosine kinase inhibitors have demonstrated encouraging results in advanced RrDTC. Nevertheless, these therapies are related with substantial side effects and a high cost. Somatostatin receptor-based therapies have shown promising findings in advanced RrDTC. Recently, prostate-specific membrane antigen (PSMA) expression was seen in advanced RrDTC in imaging studies. This study presents a case of RrDTC who was treated with 177Lu-DOTATATE and 177Lu-PSMA, presumably as a first report in this regard.
Keywords: 177Lu; DOTATATE; prostate-specific membrane antigen; radioiodine-refractory differentiated thyroid cancer